2020
DOI: 10.17344/acsi.2020.5814
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amino Acids on the Crystallization of Calcium Tartrate Tetrahydrate

Abstract: This work assesses the effects of various amino acids, including serine, alanine, methionine, and proline, on calcium tartrate tetrahydrate (CTT) crystals. The crystallization experiments were performed in batch mode at 25 °C, pH 9 with three amino acid concentrations. The CTT crystals were characterized by XRD, FTIR, SEM, particle size and zeta potential analysis. All of the amino acids used in this study were found to significantly affect the surface electrical charge, size, and morphology of the obtained cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…On the other hand, the zeta potential results of the study in 2020 by Polat et al, indicated that the addition of alanine has a remarkable effect on the surface charge of the calcium tartrate tetrahydrate (CTC) crystals, and their zeta potentials were less negative compared to the CTC crystals obtained in pure media. [ 39 ] Among the identified amino acids in Polyrhachis sp., 21 were determined (Figure 6), the most predominant one was alanine (31.5%) which could be the reason for the less negative charge of CaCO 3 @Pol compared to the neat Pol.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the zeta potential results of the study in 2020 by Polat et al, indicated that the addition of alanine has a remarkable effect on the surface charge of the calcium tartrate tetrahydrate (CTC) crystals, and their zeta potentials were less negative compared to the CTC crystals obtained in pure media. [ 39 ] Among the identified amino acids in Polyrhachis sp., 21 were determined (Figure 6), the most predominant one was alanine (31.5%) which could be the reason for the less negative charge of CaCO 3 @Pol compared to the neat Pol.…”
Section: Resultsmentioning
confidence: 99%